PERBANDINGAN KARAKTERISTIK MOTOR INDUKSI BELITAN GELUNG DENGAN BELITAN SPIRAL - Muhammad Sarjan (Foristek, 2011)
In studying the behaviour of a motor selected to drive industrial equipment, the main problem being faced is to determine whether the characteristic of the motor suits the requirements imposed by the driven unit. Different kinds of machines and mechanisms as well as electrical motor exhibit different characteristics. The aim of this research is to compare the characteristic of induction motor using loop winding and concentric winding. The parametersobserved are current, voltage, power factor, torque and speed. The experiment was conducted in the laboratory of Electrical Engineering Department of Tadulako University and the result of this study indicated that characteristic of the loop winding induction motor is better than that of theconsentric winding.